2009
DOI: 10.1007/s10995-008-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Socio-Demographic Factors Influencing the Initiation and Exclusivity of Breastfeeding in a Nigerian Semi-Urban Setting

Abstract: Low maternal education and non-utilization of orthodox obstetric facilities impairs early initiation and exclusivity of breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
68
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 15 publications
16
68
3
2
Order By: Relevance
“…Other Nigerian studies showed that maternal age and parity did not confer any advantage in breast feeding practices. 17,18 The benefits of maternal education are buttressed by the findings from this study. As the educational level increased, the likelihood of a woman breastfeeding her baby exclusively for 6 months increased.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Other Nigerian studies showed that maternal age and parity did not confer any advantage in breast feeding practices. 17,18 The benefits of maternal education are buttressed by the findings from this study. As the educational level increased, the likelihood of a woman breastfeeding her baby exclusively for 6 months increased.…”
Section: Discussionmentioning
confidence: 68%
“…In other studies conducted in other states in Nigeria, all the respondents breastfed their babies. 15,16,17,18 This is not surprising since initiation of breastfeeding is almost universal in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding has a unique biological and emotional influence on the health of both the mother and the young child [6]. It is furthermore an important determinant of infant health in the prevention of malnutrition and infections.…”
Section: Introductionmentioning
confidence: 99%
“…30 Women who had high school or higher level showed greater intent to breastfeeding. 22,25,32 A higher level of education makes mothers more able to search relevant information about optimal infant nutrition and, more likely to breastfeed their own baby.…”
mentioning
confidence: 99%